Merdeka Belajar Dalam Pandangan Filsafat Pendidikan Eksistensialisme - Al Ayyubi, Ibnu Imam; Murharyana, Murharyana; Apriyanti, Niken Siti Nur; Noerzanah, Firda; Nurfajriyah, Dewi Syifa (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
This research aims to examine in an elementary way the correlation and genealogy of a curriculum that implements independent learning for students based on the views of existentialist educational philosophy. This research uses a qualitative descriptive method with data collection techniques carried out by researchers using observation. Data analysis techniques in this research include data collection, data reduction, data presentation, and concluding. In this research, it can be concluded that freedom to learn is freedom for teaching staff and students. So it is coherent with the understanding of existentialism as a learning process that takes place based on the basic, independent curriculum of students. Thus, the relevance of philosophy in education cannot be avoided. Philosophy provides systemic, elementary, and universal direction in various educational problems to obtain the best conclusions. So, for further research, it is hoped that we can examine independent learning for students based on its relevance to philosophical figures to gain insight into complementarity in the implementation of the independent curriculum which is applied to accelerate and equilibrate with current developments.